Pengembangan Teknologi Audio dalam Pembelajaran Bahasa Arab - Wahida, Besse (AL-WARAQAH Jurnal Pendidikan Bahasa Arab, 2020)
This paper aims to determine the concept of audio media in Arabic learning and its development concept in learning listening skills. Audio media is one of the ideal choices in learning Arabic, especially in teaching listening skills / istima> 'because students can focus on the sounds they hear. In addition, this audio medium is cheaper and easier to use. Audio media is also very helpful for the shortage of educators who have small voices in delivering material, who have inappropriate intonations, or are not physically fit during the learning process. The audio media development procedure consists of four stages, namely planning, script writing, media production, and evaluation. This paper is considered important to be studied because it can be used as a material for thought for Arabic language educators in utilizing and developing the use of audio media in learning Arabic istima ', so that learning competence listening / istima' can be prioritized as an initial stage in learning Arabic.Â Keywords: Audio Technology. Arabic Learning